Incidence of traumatic cervical spine fractures in the Norwegian population: a national registry study - Fredø, Hege L (Scand J Trauma Resusc Emerg Med, 2014)
BACKGROUND: The incidence of cervical spine fractures (CS-fx) in the general population is sparingly assessed. The aim of the current study was to estimate the incidence of traumatic CS-fx and of open surgery of cervical spine injuries in the Norwegian population. METHODS: The Norwegian Patient Register (NPR) is an administrative database that contains activity data from all Norwegian government-owned hospitals and outpatient clinics. The diagnoses and procedures are coded according to the International Statistical Classification of Diseases and Related Health Problems (ICD-10) and the NOMESCO Classification of Surgical Procedures (NCSP), respectively. We retrieved information on all severe traumatic cervical spine injuries between 2009 and 2012 from the NPR. Updated information on the date of death is included through routine linkage to the General Register Office. RESULTS: Between 2009 and 2012, a total of 3 248 patients met our criteria for severe traumatic cervical spine injury. A total of 2 963 patients had one or more CS-fx, and 285 had severe non-fracture cervical spine injuries. The median age was 54 years, and 69% of the patients were male. The incidence of CS-fx and severe non-fracture injuries in the total Norwegian population was 16.5/100 000/year, and the incidence of CS-fx was 15.0/100 000/year. A total of 18% of the patients were treated with open surgery, resulting in an estimated incidence of surgery for acute traumatic cervical spine injury of 3.0/100 000/ year in the Norwegian population. The 1- and 3-month mortality rates were 4% and 6%, respectively.